1961
DOI: 10.1017/s0003356100033766
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of food intake by sheep

Abstract: 1. A series of experiments with adult sheep were carried out in an attempt to place on a quantitative basis the generalisation that the voluntary food intake of ruminants increases with the quality of the fodder they are given.2. Methods of determining voluntary intake free of subjective bias were developed. It was shown that voluntary intake varied with a fractional power of body weight close to 0·734. The length of time necessary to establish stable intakes was 12–15 days and the number of times fresh food w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
141
4
3

Year Published

1966
1966
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(165 citation statements)
references
References 8 publications
15
141
4
3
Order By: Relevance
“…It was concluded from this analysis that age is of no value in predicting forage DXVI intake. This conclusion followed from the very small differences in R ~ values (.537 and .532) between Equation []], which included age (X~), and Equation [2], which omitted X~. Likewise, gain in body weight and body weight itself contributed very little information to such a prediction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded from this analysis that age is of no value in predicting forage DXVI intake. This conclusion followed from the very small differences in R ~ values (.537 and .532) between Equation []], which included age (X~), and Equation [2], which omitted X~. Likewise, gain in body weight and body weight itself contributed very little information to such a prediction.…”
Section: Resultsmentioning
confidence: 99%
“…However, in experiments where effects on voluntary intake were measurable, it was found that varying the frequency of offering forage had little effect on the total consumption (2,11).…”
Section: Management Effects One Of the Important External Factors Afmentioning
confidence: 99%
“…The proportion of plant CWC tends to have adverse effects on voluntary intake and digestion rate. A lower digestion rate slows rate of passage of digesta through the digestive tract, and decreases rate of passage and further despresses intake (Blaxter, 1950;Blaxter et al, 1961). (Timell, 1964) .. Cellulose is usually the most abudant and insoluble polysaccharide which forms the fibrous structural backbone of CWC.…”
Section: Factors Affecting Utilization Of Low-qualitymentioning
confidence: 99%
“…Numerous experiments have been conducted on the factors controlling food intake in the ruminant, and in these experiments, variation in energy expenditure has necessarily been minimized. For instance, in a study of the hay intake of sheep in metabolism crates Blaxter, Wainman & Wilson (1961) found that the intake of food was closely related to its apparent digestibility. This general effect was also observed when sixty-R G z 9AT.…”
mentioning
confidence: 99%